A qualitative inquiry on sources of teacher efficacy in teaching low-achieving students. Issue 2 (4th March 2017) - Wang, Li-Yi; Tan, Liang-See; Li, Jen-Yi; Tan, Irene; Lim, Xue-Fang
ABSTRACT: Developing a high level of efficacy can be challenging to teachers who work with low-achieving students. The authors adopted a pragmatic qualitative research design to investigate the sources of efficacy information reported by five high-efficacy teachers and four low-efficacy teachers of secondary low-achieving students in Singapore. The results show that the psychological sources of information postulated by Albert Bandura (i.e., mastery experiences, verbal persuasion, vicarious experience, and physiological and emotional arousal), are valid but insufficient to explain high teacher efficacy. Three additional nonpsychological sources of information, including teachers' knowledge about students, rapport with students, and previous working experiences, also played significant roles in the creation of high teacher efficacy.